Optimizing Tildrakizumab Dosing in Psoriasis: A 52-Week Multicenter Retrospective Study Comparing 100 mg and 200 mg—IL PSO (Italian Landscape Psoriasis) - Mario Valenti; Luciano Ibba; Sara Di Giulio; Luigi Gargiulo; Piergiorgio Malagoli; Anna Balato; Federico Bardazzi; Francesco Loconsole; Martina Burlando; Anna E. Cagni; Norma Cameli; Carlo G. Carrera; et al. (Dermatology and Therapy)
Abstract Introduction Tildrakizumab is a monoclonal antibody targeting interleukin (IL)-23 approved for the treatment of moderate-to-severe plaque psoriasis across two different dosages (100 mg and 200 mg). The higher dosage is recommended for patients with a body weight ≥ 90 kg or a high disease burden (Psoriasis Area and Severity Index [PASI] ≥ 16 or the involvement of difficult-to-treat areas). We conducted a 52-week multicenter retrospective study to compare the effectiveness and safety of both dosages and assess their impact on specific patient subgroups. Methods We enrolled a total of 540 patients with high disease burden or body weight ≥ 90 kg; 177 and 363 were treated with tildrakizumab 200 mg and 100 mg, respectively. The effectiveness was evaluated in terms of PASI 90, PASI 100, and PASI ≤ 2 at weeks 16, 28, and 52. We also performed subanalyses according to the body weight (≥ 90 kg), PASI ≥ 16, prior biologic exposure, involvement of difficult-to-treat areas, and the presence of at least one cardiometabolic comorbidity. Results After 16 weeks of treatment, a higher proportion of patients in the 200-mg group achieved PASI 90 and PASI 100 compared to those in the 100-mg group (43.5% vs. 34.3% and 36.4% vs. 24.2%, respectively). These results were sustained at 1 year, with PASI 90 and PASI 100 reached by 68.6% and 52.9% of patients in the 200-mg group, respectively, versus 57.3% and 35% in the 100-mg group. All subgroup analyses consistently indicated a trend toward greater effectiveness with tildrakizumab 200 mg, particularly in terms of PASI 90 and PASI 100 achievement at weeks 16 and 52. No differences in the safety profile were observed throughout the study period. Conclusion Our findings confirm the superior effectiveness of tildrakizumab 200 mg over 100 mg in specific subgroups of patients with a comparable safety profile across the study period.